A Comprehensive Approach to Born-Digital Archives - Carroll, Laura; Farr, Erika; Hornsby, Peter; Ranker, Ben (Archivaria, 2011)
This paper discusses how the arrival of born-digital content into archives has both dictated innovations in archival practice and promises to bring significant change to research methodologies. As a collection’s scope moves from discrete files to operating systems and complex digital collections, archives must build upon practices developed over recent decades in the handling of electronic records while also radically reconsidering the extent of acquisition and approaches to access. These changes are discussed within the context of the manuscripts and computers that comprise Salman Rushdie’s personal literary “papers,” which are housed in Emory University’s Manuscript, Archives, and Rare Book Library (MARBL). Early in the development of the Rushdie project, the library made a commitment to approach the material as holistically as possible, to prioritize the integration of paper and digital, and to balance the needs of donors with those of researchers. The paper will outline how the library developed researcher tools that allow concurrent exploration of the paper material and the born-digital material via emulation and item-level, databasedriven searches. RÉSUMÉ Ce texte explore comment l’arrivée aux archives de contenu créé dès l’origine sur support numérique a engendré des innovations dans la pratique archivistique et promet d’apporter des changements importants aux méthodologies de recherche. Alors que l’étendue d’une collection se déplace de fichiers isolés (« discrete files ») vers des systèmes d’exploitation et des collections numériques complexes, les institutions d’archives doivent se fonder sur les pratiques développées au cours des dernières décennies pour manipuler des documents numériques, tout en repensant radicalement la quantité des acquisitions et les approches relatives à l’accès. Ce texte aborde ces changements dans le contexte des manuscrits et des ordinateurs qui font partie des « manuscrits » littéraires personnels de Salman Rushdie, conservés à la Manuscript, Archives, and Rare Books Library (MARBL) de la Emory University. Très tôt dans le développement du projet Rushdie, la bibliothèque s’est engagée à approcher ce matériel de façon aussi holistique que possible, à donner la priorité à l’intégration du papier avec le numérique et à établir un équilibre entre les besoins du donateur et des chercheurs. Ce texte montrera comment la bibliothèque a développé des outils de recherche qui permettent de repérer à la fois le matériel en format papier et le matériel créé en format numérique, et cela grâce à l’émulation et à la recherche au niveau de l’item à partir de bases de données.